Academic Culture Shock Workshop as a Strategy to Improve Students'Mental Readiness in the Academic Environment of the Faculty of Medicine - Rugebregt, Joanne; Rugebregt, Joanne Marrijda; Noya, Farah Christina; Saija, Alessandra Flowrence; Safutra, Muhamad Sadam; Wade Marlinda; Huwae, Laura Bianca Sylvia; Bension, Johan Bruiyf (Devotion : Jurnal Pengabdian Psikologi, 2025)
.